Convergence rates in regularization for the case of monotone perturbations - Nguen, Byong (Ukrains’kyi Matematychnyi Zhurnal, 2000)
Convergence rates are justified for regularized solutions of a Hammerstein operator equation of the form x + F 2 F 1(x) = f in the Banach space with monotone perturbations f 2 h and f 1 h .